On the Integer Solution of the Transcendental Equation (Indian Journal of Advanced Mathematics (IJAM), 2024)
Let C be a positive non-square integer. In this paper, we look at the complete solutions of the Transcendental equation where x2-cy2-a2 or 22t. In addition, we find repeated relationships in the solutions to this figure.